P–615 The effect of late-follicular phase progesterone rise on embryo ploidy, embryo quality and cumulative live birth rates following a freeze-only strategy. (6th August 2021) - Neves, A R; Santos-Ribeiro, S; Garcí. Martínez, S; Soares, S; García-Velasco, J A; Garrido, N; Polyzos, N P
Abstract: Study question: Is late-follicular phase progesterone elevation (PE) associated with a deleterious effect on embryo euploidy, embryo blastulation and cumulative live birth rates (CLBRs)? Summary answer: Late-follicular phase PE has no impact on impact on embryo euploidy rate, embryo blastulation rate nor on the CLBR. What is known already: The effect of PE in ART outcomes has been extensively studied, yielding so far conflicting results. While some authors claim it is only detrimental to endometrial receptivity, others have suggested that it may also impair oocyte/embryo quality. Moreover, little is known regarding the potential effect PE may have on embryo ploidy and, consequently, CLBR. Study design, size, duration: A multicenter retrospective cross-sectional study was performed between August 2017 and December 2019. A total of 1495 ICSI cycles coupled with preimplantation genetic diagnosis for aneuploidies (PGT-A) and deferred frozen embryo transfer (FET) were analyzed. Participants/materials, setting, methods: All patients underwent ovarian stimulation with GnRH antagonist protocol and performed a serum progesterone measurement at one of the participating private fertility clinics on the day of trigger. The sample was stratified according to the progesterone levels: normal (≤1.50 ng/ml) and high (>1.50 ng/ml). The primary outcome was the embryo euploidy rate. Secondary outcomes were the number of euploid blastocysts, the blastulation rate and CLBR. Main results and the role of chance: Late-follicular phase PE was associated with higher late-follicular estradiol levels (2847.56±1091.10 pg/ml vs. 2240.94± 996.37 pg/ml, p < 0.001) and more oocytes retrieved (17.67±8.86 vs. 12.70±7.00, p < 0.001). The number of euploid embryos was higher in the PE group (2.32±1.74 vs. 1.86±1.42, p < 0.001), whereas the embryo euploidy rate (48.3% [44.9%–51.7%] vs. 49.1% [47.7%–50.6%] and blastulation rate (47.1% [43.7%–50.5%] vs. 51.0% [49.7%–52.4%]) were comparable between the two groups. Likewise, no significant differences were found regarding the live birth rate (LBR) after the first FET (34.1% vs. 31.1%, p = 0.427) nor the CLBRs (38.9% vs. 37.0%, p = 0.637). Mixed-model analysis was performed in order to account for the clustering of cycles in the same patient. Adjusting for patients' age, PE and BMI, PE failed to demonstrate any effect on the embryo euploidy rate (OR 1.03 [95% CI 0.89–1.20]). Mixed-model analysis for the number of euploid embryos was also performed. After adjusting for PE, age, BMI and ovarian response, PE did not affect the number of euploid embryos (0.02 [95%CI –0.21;0.25]. Multivariate logistic regression adjusted for PE, age, BMI and ovarian response revealed that PE was not associated with the CLBR (adjOR 0.96 [95% CI 0.66–1.38]). Limitations, reasons for caution: Limitations of the study include its retrospective nature. Moreover, including only GnRH antagonist protocol and ICSI does not allow the extrapolation of these results to other populations. Wider implications of the findings: Our findings question results from previous studies claiming a detrimental effect of PE on embryo implantation potential. According to our results, PE has no impact on embryo euploidy rate, blastulation rate nor on CLBRs. Trial registration number: Not applicable